The Conceptual Foundations of Vojin Matić's Paleopsychology in the Context of Serbian Ethnology - Marko Teodorski (University of Belgrade, 2021)
Vojin Matić was a leading figure in Serbian post-war psychoanalysis, particularly in the 1950s and 1960s. Paleopsychology, looked upon extremely favorably, even in a revolutionary way, by the Serbian psychoanalysts of the time, was the last and indisputably most problematic part of his oeuvre. The absence of necessary anthropological methodology, the uncritical adoption of discredited and rejected concepts (such as matriarchy), the promotion of 19th-century unilineal evolutionism viewing prehistory as the childhood of mankind – these are just some of the problems of Matić's paleopsychological oeuvre. Nevertheless, this did not prevent him from leaving an indelible imprint on the thinking of numerous generations which would go on to position Serbian psychoanalysis on the international stage. Although untenable by contemporary anthropological standards, Matić's paleopsychology is interwoven with the Serbian psychoanalysis of the 1970s and 1980s, exerting a decisive influence on its application in the humanities, from Vladeta Jerotić's psychoanalytical culturology to Zoran Gluščević's literary criticism. Matić, in turn, actively adopted some outdated positions from the Serbian ethnology of the time. By providing this broader theoretical, historical and academic context, the paper seeks to shed light not only on the occurrence of this scientifically questionable theory, but also on its (surprisingy "uncritical") acceptance outside the anthropological community. The paper therefore presents, in turn: 1) the tenets of Matić's paleopsychology, with emphasis on the features it shared with contemporary anthropology; 2) the biographical and disciplinary/historical background of paleopsycholgy in the works of world psychoanalysts and anthropologists, and in the practices of Serbian ethnology; it is pointed out that Matić's paleopsychology merely provided a psychoanalytic perspective to conventional Serbian ethnology; 3) a reading of Matić's paleopsychological system as a "strong" paranoid theory, that is to say, a theory which, through specific mechanisms os associativity and anticipation, absorbs every ethnographic, anthropological and archaeological fact, thus metastasizing into a self-contained and hermetic system (something that Matić himself noted as a possible structure of his own thinking).